Pretreatment strategies for enhanced biogas production from lignocellulosic biomass - Abraham, Amith; Mathew, Anil K; Park, Hyojung; Choi, Okkyoung; Sindhu, Raveendran; Parameswaran, Binod; Pandey, Ashok; Park, Jung Han; Sang, Byoung-In (Bioresource technology, 2020)
The inclusion of a pretreatment step in anaerobic digestion processes increases the digestibility of lignocellulosic biomass and enhances biogas yields by promoting lignin removal and the destruction of complex biomass structures. The increase in surface area enables the efficient interaction of microbes or enzymes, and a reduction in cellulose crystallinity improves the digestion process under anaerobic conditions. The pretreatment methods may vary based on the type of the lignocellulosic biomass, the nature of the subsequent process and the overall economics of the process. An improved biogas production by 1200% had been reported when ionic liquid used as pretreatment strategy for anaerobic digestion. The different pretreatment techniques used for lignocellulosic biomasses are generally grouped into physical, chemical, physicochemical, and biological methods. These four modes of pretreatment on lignocellulosic biomass and their impact on biogas production process is the major focus of this review article.